Factors Influencing Tax Compliance Behavior among the Industries of Butwal Industrial Estate - Dumre, Durga Prasad; Shrestha, Lalit Man (The Lumbini Journal of Business and Economics, 2023)
This study attempts to investigate the factors influencing tax compliance behavior in all the industries with the number 72 of Butwal Industrial Estate (BIE) to determine whether taxpayers perceived fairness, social norms, accounting practice, and government fiscal responsibility affect the tax compliance behavior of the owners of the BIE. The questionnaire was distributed to all industries of BIE. Where 46 only responded. Cross-sectional survey research design was used, and data was obtained from primary sources. The results have been drawn by using descriptive and inferential statistics. The study’s findings show that accounting practice and government fiscal responsibility have a significant relationship with tax compliance behavior in BIE and an insignificant relationship between social norms and taxpayers’ perceived fairness in tax compliance. The study recommends that BIE owners ensure that their accounting record system is correct and that the government is allowed to use tax revenue for the benefit of society.